Air quality index – A comparative study for assessing the status of air quality before and after lockdown for Meerut. (2022) - Kumar, Gaurav; Kumar, Saurabh; Suman,
Abstract: Air Quality Index is the simplest and widely used measure of overall air pollution of a region. Air Quality Assessment can be done with the help of Air Quality Index Parameter. Essentially it is used for assessing the air pollution hot spots in the region for delineating management and concrete actions. Different Methodology are adopted to assess the Quality of air for study area by taking into consideration of four pollutants synergistic effects which are PM10, PM2.5, SO2 and NO2 The average concentration recorded for PM10, PM2.5, SO2 and NO2 was recorded for six consecutive months before and after the lockdown period i.e., from 25th December 2019 till 25th June 2020. Different AQI were estimated for various months and varying results were observed ranging from good to unacceptable for the set of data. The findings of this study will provide detailed information of air pollution and AQI status before and after lockdown.